2010
DOI: 10.1111/j.1365-2842.2009.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the unilateral TMJ osteoarthritis/osteoarthrosis, mandibular asymmetry and the EMG activity of the masticatory muscles: a retrospective study

Abstract: The purpose of this retrospective study was to investigate the relationship between the unilateral temporomandibular joint (TMJ) osteoarthritis/osteoarthrosis (OA), mandibular asymmetry and electromyographic (EMG) activity of the masticatory muscles. Twenty-two Japanese women (aged 23.2 +/- 5.4 years) and 10 Japanese men (aged 22.4 +/- 2.8 years) exhibiting unilateral TMJ OA were included in this study. Two angular and seven linear measurements were obtained for the analysis of the skeletal hard tissues. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…The result showed the MD group and DD group had no difference but the AR group had a statistically significant difference (p<0.01). This upholds the connection between unilateral OA and facial asymmetry, keeping up with the earlier reports of Matsumoto et al 20) In animal research, the ablation of the articular disc decreases the ramus height, thus leading to a mandibular midline shift on the affected side. 29) These results suggest that unilateral TMJ OA may result in a shortened vertical between the mandibular asymmetry and TMD so to adopt proper diagnostic criteria for TMD and asymmetry itself.…”
Section: )supporting
confidence: 60%
See 2 more Smart Citations
“…The result showed the MD group and DD group had no difference but the AR group had a statistically significant difference (p<0.01). This upholds the connection between unilateral OA and facial asymmetry, keeping up with the earlier reports of Matsumoto et al 20) In animal research, the ablation of the articular disc decreases the ramus height, thus leading to a mandibular midline shift on the affected side. 29) These results suggest that unilateral TMJ OA may result in a shortened vertical between the mandibular asymmetry and TMD so to adopt proper diagnostic criteria for TMD and asymmetry itself.…”
Section: )supporting
confidence: 60%
“…However, the cause and effect relationship among TMJ OA, the masticatory muscle function, and the dentofacial morphology could not be elucidated. 20) It is still controversial whether asymmetry affects the occurrence of TMDs. It might be partly because, although age and gender is well known to affect the occurrence of TMDs, such factors were not properly controlled for analysis in most previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TMJOA may differ from OA in knee or hip, which is closely related to aging, obesity, and overload (Herrero-Beaumont et al 2009). Overload of the TMJ, including severe malocclusion, skeletal jaw asymmetry, and muscle overuse, has been considered one of the main causes for TMJOA (Tanaka et al 2008;Matsumoto et al 2010;Krisjane et al 2012), but the majority of TMJOA is difficult to attribute to overload. Therefore, the causes of impaired condylar cartilage in the TMJ remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6 Concurrently, temporomandibular disorders have been demonstrated to induce mandibular asymmetry. [7][8][9][10] A study conducted by Emshoff et al, 11 has shown that TMJ disc displacements without reduction and osteoarthrosis are important determinants of mandibular backward positioning. Disc displacement might induce skeletal changes in facial morphology.…”
Section: Introductionmentioning
confidence: 99%